Spontaneous splenic rupture: an unusual cause of hypovolaemia. Issue 4 (July 1996) - Birkinshaw, R; Saab, M; Gray, A
Abstract : Splenic rupture in infectious mononucleosis is an extremely rare but often fatal complication. A case presented to the accident and emergency department in ventricular fibrillation seconds after losing signs of any cardiac output. The underlying cause of cardiorespiratory arrest always be sought irrespective of the presenting rhythm.